Removal of Pb²⁺ Ions Using Rice Husk Ash and Metakaolin Based Geopolymer - Fatikhah Cahyani; Della Arthamevia; Srie Muljani; Caecilia Pujiastuti; Ketut Sumada (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Heavy metal contamination in aquatic environments is a serious environmental issue due to its toxicity, persistence, and tendency to accumulate within living organisms. One promising approach to address this problem is adsorption using aluminosilicate-based geopolymers. This study aimed to evaluate the ability of rice husk ash and metakaolin-based geopolymers to remove Pb²⁺ ions and to investigate the effects of Si/Al molar ratio and NaOH concentration on geopolymer characteristics, removal efficiency, and adsorption capacity. Geopolymers were synthesized using rice husk ash as a silica source and metakaolin as an alumina source with varying Si/Al molar ratios and NaOH concentrations. The synthesized geopolymers were characterized using SEM-EDX and FTIR, while their adsorption performance was evaluated based on Pb²⁺ removal efficiency and adsorption capacity from Pb(NO₃)₂ solution. The results demonstrated that the geopolymer was successfully synthesized and showed potential as an effective adsorbent for Pb²⁺ removal. SEM-EDX and FTIR analyses confirmed the formation of an aluminosilicate structure and indicated that Pb²⁺ adsorption involved ion-exchange mechanisms and interactions with active functional groups on the geopolymer surface. Variations in the Si/Al molar ratio and NaOH concentration significantly affected the characteristics and adsorption performance of the geopolymer. The optimum adsorption condition was achieved at a Si/Al molar ratio of 4.2 and a NaOH concentration of 10 M, resulting in an adsorption capacity of 7.94 mg/g and a removal efficiency of 99.83%.